Positive Supervisor Behaviors and Employee Performance: The Serial Mediation of Workplace Spirituality and Work Engagement - De Carlo, Alessandro; Dal Corso, Laura; Carluccio, Francesca; Colledani, Daiana; Falco, Alessandra (Frontiers in Psychology, 2020)
Organizational research has highlighted the crucial role of supervisors in promoting employee well-being and performance. According to the motivational approach, supervisors positively influence employees’ outcomes by enhancing their positive feelings. In this study, we examine how positive supervisor behaviors may improve employee performance through the serial mediation of workplace spirituality and work engagement. Data were collected from 330 Italian employees. Results showed that supervisor integrity and responsible behaviors have a positive effect on employee performance directly; moreover, positive supervisor behaviors influence performance indirectly, through both the partial mediation of work engagement and the serial mediation of workplace spirituality and work engagement. The present study highlighted that supervisors should behave responsively and honestly to trigger a virtuous motivational process in their employees, which leads to boost their performance. The practical implications of these findings are discussed.